Analysis of Students' Interest in English Songs as a Media for Listening Learning - Riska Humaera; Nurdin Noni; Yunitari Mustikawati (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Listening ability is one of the basic skills in learning English that is often considered difficult by students. This is caused by several factors such as lack of understanding, the speed of native speakers, and monotonous learning materials. To overcome this, innovative and interesting learning media are needed. One of the media that is considered effective and close to the world of teenagers is English songs. Songs not only present authentic language, but are also able to create a pleasant learning atmosphere. Based on this background, this study aims to determine the interest of class XI Harmonis students in the use of English songs in listening learning.This study uses a quantitative descriptive approach. The instrument used is a closed questionnaire consisting of 12 statements, each with four answer choices scored 1–4. The research subjects were 30 class XI Harmonis At SMAN 1 Pangkep. The data were analyzed to determine the total score, percentage, and classification of student interest levels based on certain intervals.The results of the study showed that 23 students (77%) were in the high interest category (Very High Interest) and 7 students (23%) were in the very high interest category (Very High Interest). There were no students in the medium or low interest category. This shows that the use of English songs is very popular with students and can be an effective medium in listening learning. The conclusion of this study is that English songs have great potential to increase students' interest in learning to listen. Therefore, it is recommended that English teachers consider the use of songs as part of a learning strategy, by choosing songs that are appropriate to the level of ability and interest of students so that learning becomes more enjoyable, meaningful, and effective